Exploiting Base Excision Repair to Improve Therapeutic Approaches for Pancreatic Cancer - Sharbeen, George; McCarroll, Joshua; Goldstein, David; Phillips, Phoebe A. (Frontiers in Nutrition, 2015)
Pancreatic ductal adenocarcinoma (PDA) is a highly chemoresistant and metastatic disease with a dismal 5-year survival rate of 6%. More effective therapeutic targets and approaches are urgently needed to tackle this devastating disease. The base excision repair pathway has been identified as a predictor of therapeutic response, prognostic factor and therapeutic target in a variety of cancers. This review will discuss our current understanding of base excision repair in PDA and its potential to improve PDA treatment.